Structure–Function Decoupling: A Novel Perspective for Understanding the Radiation-Induced Brain Injury in Patients With Nasopharyngeal Carcinoma - Kang, Ya-fei; Chen, Rui-ting; Ding, Hao; Li, Li; Gao, Jian-ming; Liu, Li-zhi; Zhang, You-ming (Frontiers in Neuroscience, 2022)
Radiation-induced functional and structural brain alterations are well documented in patients with nasopharyngeal carcinoma (NPC) following radiotherapy (RT); however, alterations in structure-function coupling remain largely unknown. Herein, we aimed to assess radiation-induced structure-function decoupling and its importance in predicting radiation encephalopathy (RE). We included 62 NPC patients (22 in the pre-RT cohort, 18 in post-RT-RE_{+ve} cohort and 22 in post-RT-RE_{-ve} cohort). A metric of regional homogeneity (ReHo)/voxel-based morphometry (VBM) was used to detect radiation-induced structure-function decoupling, which was then used as a feature to construct a predictive model for RE. Compared with the pre-RT group, patients in the post-RT group (which included post-RT-RE_{+ve} and post-RT-RE_{-ve}) showed higher ReHo/VBM coupling values in the substantia nigra (SN), putamen. and bilateral thalamus and lower values in the brain stem, cerebellum, bilateral medial temporal lobes, bilateral insula, right precentral and postcentral gyri, medial prefrontal cortex (MPFC), and left inferior parietal lobule (IPL). In the post-RT group, negative correlations were observed between maximum dosage of RT (MDRT) to the ipsilateral temporal lobe and ReHo/VBM values in the ipsilateral middle temporal gyrus. Moreover, structure-function decoupling in bilateral superior temporal gyrus (STG), bilateral precentral and postcentral gyri, paracentral lobules, right precuneus and IPL, and right MPFC exhibited excellent predictive performance (accuracy = 88.0%) in identifying patients likely to develop RE. These findings show that ReHo/VBM may be a novel effective imaging metric that reflects the neural mechanism underlying RE in patients with NPC.